IMAGE, INTERPRETATION AND ARTISTIC PSYCHOLOGY - Toshpo`latova, Dilorom (Журнал иностранных языков и лингвистики, 2021)
In this article, Ulugbek Hamdam's novel "Equilibrium" is analyzed as a realist work, in turn, the problems of image, interpretation and artistic psychology, the harmonization of soul, spirit and mind senses in the psychological processes of heroes such as Muhammad brother, Joseph, Amir, Sadiq. The logic - responsibility logic, which is integrated into the spirit of the novel, is not only the notion that each hero is responsible for himself, at least for his loved ones, for those who gave birth to a child, a neighbor, glue, a nation, the leadership of the country towards such high ideas begins on the threshold of yoinki Vatan – uya, the purvikor